Influence of the Type of Breastfeeding and Human Milk Polyamines on Infant Anthropometric Parameters - Muñoz-Esparza, Nelly C.; Vásquez-Garibay, Edgar M.; Guzmán-Mercado, Elizabeth; Larrosa-Haro, Alfredo; Comas-Basté, Oriol; Latorre-Moratalla, M. Luz; Veciana-Nogués, M. Teresa; Vidal-Carou, M. Carmen (Frontiers in Nutrition, 2022)
Feeding choices in the early months of life are key determinants of growth during infancy. Polyamines participate in cell proliferation and differentiation, and it has also been suggested that polyamine metabolism plays a role in adipogenesis. As the main exogenous source of polyamines in the infant is human milk, the aim of this work was to study if the type of breastfeeding received and the polyamine intake from human milk has an influence on infant anthropometric parameters. A cohort of 78 full-term healthy newborns was followed up until four months of age; 55 were fully and 23 partially breastfed. Anthropometric measurements were taken at two and four months, when human milk samples were also collected for analysis of polyamine content by UHPLC-FL. Fully breastfed infants had a better anthropometric profile than those partially breastfed (p< 0.05). Furthermore, polyamine intake in partially breastfed infants was significantly lower compared to those fully breastfed. However, only two of the fifteen anthropometric indicators evaluated (triceps skinfold and mean upper arm circumference) showed a significant inverse association with polyamine content in human milk and intake (p<0.05). Infant growth and body composition differ according to the type of breastfeeding received. Based on the weak associations between polyamines and anthropometric indicators, it is not possible to conclude the influence of polyamines in infant growth and body composition.